Pemanfaatan Limbah Cangkang Kerang Lokan (Glonia Erosa) Sebagai Bahan Penjernih Air - Amana, Wahyu; Dharta, Yuli; Tuparjono, Tuparjono; Wahyudie, Ilham Ary (Jurnal Inovasi Teknologi Terapan, 2024)
Lokan mussels (Geloina erosa) live at the bottom of sandy and muddy waters. Lokan shell waste is found on many Indonesian beaches and is left unattended by the surrounding community, so a new breakthrough is made to add value to the use of the shell. this study aims to convert waste into materials that can increase pH in water, because there are calcium carbonate (CaCO3) compounds that are useful in the adsorption process. Adsorption is the process of absorbing substances or content such as iron metal (Fe). The pores on the surface of the shell can carry out the adsorption process using a physical method, namely heating at 250 oC and 350 oC to open the pores on the surface. The result of this test is that the shells of lokan shells made and then tested for Ph in water mixed with powder have an increase in value from 5.7 to 7.4 - 8.2. In elemental testing or (XRF) for the lokan shell itself there is the element CaO or Calcium oxide after heating.